Pemberdayaan Motorik Kasar Anak Melalui Senam Anak Sholeh di RA Nurul Washilah Simpang Marbau Kecamatan NA IX.X - Khairani Khairani; Eva Khoirani Berutu (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2022)
This study aims to determine the movements performed in pious children's gymnastics in order to develop children's gross motor skills. Knowing the implementation of pious children's gymnastics. To find out how the teacher trains the correct gross motor movements in pious children's gymnastics at RA Nurul Washilah, Simpang Merbau Village, Na IX.X District. This study uses a qualitative method. The data collection procedure is by using the method of observation, interviews and documentation. Based on the results of the study, the movements carried out in pious children's gymnastics to develop gross motor skills for RA Nurul Washilah's children, Simpang Merbau Village, Na IX.X District, were jumping, running, walking, tiptoeing, moving the whole body, hands and feet. In addition to the movement that is useful for developing gross motor skills, this pious child's gymnastics is also full of Islamic values, both in poetry and in movements. Therefore, RA Nurul Washilah chose this exercise among other children's gymnastics. The implementation of pious children's gymnastics at RA Nurul Washilah, Simpang Merbau Village, Na IX District. carried out since 2018. They realize it every Friday and Saturday, because other days iqra' activities are carried out. As for the steps for implementing pious children's gymnastics, at the initial stage the teacher prepares gymnastic equipment such as tape and gymnastic music. Then prepare a line of children. Giving direction and motivating the children. Next, a gymnastics was held where some of the teachers became instructors in front of the children. The way the teacher trains the correct gross motor movements in pious children's gymnastics at RA Nurul Washilah, Simpang Merbau Village, Na IX.X District is by exemplifying the movements of jumping, walking and running. The teacher also adjusts the position of the child, so that the child's movements can run well. Initially, some children could not do gymnastics well, where the movements made by children were still stiff, there were also children who did gymnastics movements just carelessly and still wanted to play. And the teacher is aware of this, therefore the teacher also teaches gymnastics for pious children in class. And the results are visible during the three months of the research, where the movements of children in pious children's gymnastics are getting better. Keywords: Gross Motor, Sholeh Anak Children's Gymnastics